Developing the indonesian government enterprise architecture framework appropriate for Indonesian government agencies - Asbartanov Lase; Benny Ranti (Institute of Advanced Engineering and Science, 2019)
This research was conducted to develop the Indonesian Government Enterprise Architecture (IGEA) framework which is suitable for Indonesian government agencies. Due to their complexity and expensive implementation cost, existing EA frameworks such as TOGAF and Zachman have so far not been the choice for building GEA by some countries including Australia and New Zealand. Those countries have built their own GEA namely Australia’s AGA and New Zealand’s GEA-NZ, respectively. Learning from this experience, the authors did a research to build Indonesia’s GEA or IGEA. This paper explains the research process which starts from mapping or comparing TOGAF, AGA, and GEA-NZ frameworks to get the underlying foundation for building GEA, analyzing framework artifacts, to building IGEA by adding specific Indonesian regulations and policies such as RPJMN and Nawacita. This IGEA framework is expected to become a reference for developing EA not only at institutional level but also the most important thing at national or cross institutional level, in order to increase the effectiveness of government IT spending.